Antifungal activity of chitosan in Cladosporium cladosporioides isolated from safflower - Eber A. Quintana-Obregón (Revista Mexicana de Micología, 2011)
The chitosan showed inhibition of spore germination at 24 h on Cladosporium cladosporioides (70.99 ± 12.53 and 32.72 ± 10.85% for QB and QA, chitosans, respectively). Chitosan caused morphometric changes on spore evidenced by excessive swelling and delay on the germ tube. However, in comparison with the controls, the chitosan not inhibited the colony radial extension rate.